1964
DOI: 10.1037/h0039933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UCS intensity on the acquisition and extinction of an avoidance response.

Abstract: 123 naive female albino rats were given 30 trials a day for 4 days on a shuttle-box avoidance task. Different groups received 0.5, 1.0, 1.5, 2.5, 3.0, 3.5, and 4.5 ma. of shock during training. The results showed that relatively intense shock interferes with the acquisition of both escape and avoidance responses. Learning falls off rapidly after 1.0 ma. and is probably maximally disrupted at about 2.5 ma. with further increase in intensity having relatively limited additional effect up to 4.5 ma., the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
54
4

Year Published

1968
1968
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(70 citation statements)
references
References 11 publications
12
54
4
Order By: Relevance
“…The effects of increased shock level in training are well documented and are known to depend on the particular behavioral requirements of the avoidance training procedure. In the two-way shuttle box shock increases cause disruption of avoidance responding (Moyer & Korn 1964;Levine 1966;McAllister, McAllister, & Douglas, 1971). Varying extinction response levels in this manner aim to test the peptide's effects over a wider range of response baselines.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of increased shock level in training are well documented and are known to depend on the particular behavioral requirements of the avoidance training procedure. In the two-way shuttle box shock increases cause disruption of avoidance responding (Moyer & Korn 1964;Levine 1966;McAllister, McAllister, & Douglas, 1971). Varying extinction response levels in this manner aim to test the peptide's effects over a wider range of response baselines.…”
Section: Methodsmentioning
confidence: 99%
“…As an illustration, relatively strong shock has been repeatedly shown to inhibit avoidance acquisition (D ' Amato & Fazzaro, 1966;Moyer & Korn, 1964). Recent research in our laboratory has demonstrated that strong shock profoundly inhibits anticipatory responding, the magnitude of the effect being sufficient to account for the influence of shock intensity on avoidance acquisition (D'Amato, Etkin, & Fazzaro, in press).…”
mentioning
confidence: 99%
“…1_ DISCUSSION Guinea pigs trained with low shock improved at a greater rate and reached a higher final level of performance than did animals trained under medium or high shock. In this respect, guinea pigs appear to behave Iike rats (Moyer & Korn, 1964;Levine, 1966)_ It is not certain why Webster et al (1965) failed to find this relation, but it is possible that their low shock (0.4 mA, also from a Grason-Stadler 6070B shock generator), which should have produced the best performance, was simply too low to motivate learning adequately _ Dur preliminary work indicated that 1.5 mA was about the lowest shock intensity that would produce prompt and reliable escape behavior. (Guinea pigs appear to be very much less sensitive to foot shock than do rats_)…”
mentioning
confidence: 99%
“…Rats in a two·way shuttlebox typically avoid more frequently at low shock intensities than at high intensities (Moyer & Korn, 1964;Levine, 1966). Webster,Brimer,& Evonic (i 965), however, found no relatioh between avoidance performance and shock intensity using guinea pigs.…”
mentioning
confidence: 99%